PENGARUH UPAH DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERASI (Survei pada CV Aji Bali Jaya Wijaya di Surakarta) - Stefanus Bagi Lalu Pada, Lamidi & Sumarno Dwi Saputra (Universitas Slamet Riyadi, 2017)
The purpose of research is to analyze the significance of the effect of wages,working environment and motivation on employee performance in CV Aji BaliJayawijaya in Surakarta. Analyzing motivation moderating effects on wage and workingenvironment influences the performance of employees at CV Aji Bali Jayawijaya inSurakarta. This study uses survey method, the type of data used quantitative andqualitative data, the data source used primary data and secondary data. Population andsample in this study were all employees of CV Aji Bali Jayawijaya totaling 55 people, sothis study is a census study. Data collection methods are used: questionnaires andobservations. Data analysis technique used to test the validity, reliability test, classicassumption test, multiple linear regression analysis, and test the absolute difference. Inconclusion, that there is a significant influence wages, working environment andmotivation on employee performance in CV Aji Bali Jayawijaya in Surakarta.Motivation does not moderate the influence wages and working environment toemployees performance at CV Aji Bali Jayawijaya in Surakarta. The dominant variableinfluence on employee performance is variable wages, since most large regressioncoefficient, regression coefficient between independent variables work environment andwork motivation.Keywords: salary, work environment, motivation, employee performance